The Relationship Between Work-Family Conflict, Emotional Regulation, and Psychological Well-Being Among Working Mothers at PT X - Lina Marliana; Prinskadamara Satri; Ridlwan Muttaqin (Dinasti Research, 2026)
This study was conducted to analyse the relationship between work-family conflict and emotional regulation on psychological well-being among working mothers who serve as the primary breadwinners at PT X. The study employed a quantitative approach using a descriptive correlational method and multiple linear regression analysis. Based on the results of the Pearson Product Moment correlation test for the work-family conflict variable, a correlation coefficient of 0.177 was obtained with a significance value of 0.175 (p > 0.05). These results indicate that no significant relationship was found between work-family conflict and psychological well-being among working mothers acting as female breadwinners at PT X. Meanwhile, emotional regulation showed a positive and significant relationship with psychological well-being, with a significance level of 0.000 (p < 0.05) and a correlation coefficient of 0.996. This finding indicates that the ability to manage and control emotions plays a crucial role in enhancing the psychological well-being of working mothers. The results of the simultaneous test (F-test) also showed that work-family conflict and emotional regulation together have a significant relationship with psychological well-being, with a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.993. Emotional regulation is therefore the most influential factor in helping working mothers, as female breadwinners, maintain psychological stability amidst the demands of work and family life.